Method for producing crystals of a phenolic compound having a methoxymethyl group
Patent Information
- Application Number
- TW114136223
- Authority / Receiving Office
- TW · TW
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-07-08
- Filing Date
- 2025-09-19
- Publication Date
- 2026-08-16
- Estimated Expiration
- 2045-09-18
AI Technical Summary
Existing methods for producing phenolic compounds with methoxymethyl groups are unsuitable for large-scale industrial production due to slow crystallization processes and unclear properties of the resulting compounds, making them difficult to manufacture efficiently.
A crystallization method using a specific solvent combination of a chain aliphatic alcohol with 3 to 4 carbon atoms and an aliphatic hydrocarbon solvent with 6 to 8 carbon atoms, which facilitates rapid crystal precipitation and high yield, suitable for industrial manufacturing.
The method achieves faster crystal precipitation and high yield, making it suitable for efficient industrial production of phenolic compounds with methoxymethyl groups.
Smart Images

Figure TWG2TA001072610_001 
Figure TWG2TA001072610_002 
Figure TWG2TA001072610_003
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for manufacturing crystals of phenolic compounds having a methoxymethyl group. More specifically, it relates to a method for manufacturing crystals including a crystallization step for producing crystals of a compound represented by the following chemical formula (A1) (hereinafter sometimes referred to as compound A1). [Previous Technology]
[0002] Phenolic compounds containing hydroxymethyl or methoxymethyl groups have conventionally been used as curing agents for resins containing phenolic hydroxyl groups or as crosslinking agents to improve the film properties of photosensitive resins. Regarding phenolic compounds containing methoxymethyl groups, compounds represented by chemical formula (A1) (compound A1) are known. Regarding conventionally known methods for isolating compounds represented by chemical formula (A1), Patent Document 1 describes a method in which a hexahydroxymethyl compound (compound B described later), as a precursor of the compound, is reacted with methanol to synthesize compound A1, and the methanol is removed by vacuum distillation to achieve isolation. Patent Document 2 describes a method for synthesizing 2,6-dimethoxymethylphenol (III) from 2,6-xylenol as a starting material, through acetylation, bromination of methyl groups, and methoxylation of bromomethyl groups. Compound A1 is then synthesized by condensing the acetylated form of 2,6-dimethoxymethylphenol (III) with 2,6-dimethoxymethylphenol (III) and then deacetylation. It also describes a method of crystallization with ethanol as a post-reaction isolation method. Patent Document 3 describes concentrating a 20% propylene glycol monomethyl ether (PGME) solution of 80% purity compound A1 in an evaporator to form a 50% propylene glycol monomethyl ether solution, and then allowing it to stand for 2 days to obtain white crystals of compound A1. Patent Document 4 describes concentrating a 20% ethyl lactate solution of compound A1 in an evaporator to form a 40% ethyl lactate (EL) solution, and then allowing it to stand at room temperature for 5 days to obtain a pale orange solid of compound A1. Patent Document 5 describes several manufacturing examples of compound A1. Examples 5, 15, and 16 describe the manufacture of solutions containing γ-butyrolactone with different compositions and solute concentrations for compound A1, its dimers, and trimers. Furthermore, in synthesis example 17, similar to Patent Document 4, a 20% ethyl lactate solution of compound A1 is concentrated in an evaporator to form a 50% ethyl lactate solution, and then left to stand for two days to obtain white crystals of compound A1. [Prior Art Documents] [Patent Documents]
[0003] [Patent Document 1] International Publication No. 2024 / 082896 [Patent Document 2] Chinese Patent Application Publication No. 115959977 [Patent Document 3] International Publication No. 2016 / 148176 [Patent Document 4] Japanese Patent Application Publication No. 2009-227697 [Patent Document 5] Japanese Patent Application Publication No. 2024-52592 [Summary of the Invention]
[0004] [Problems to be Solved by the Invention] The properties of compound A1 obtained by the isolation method described in Patent Document 1 are unclear. Since it is a distillation residue obtained by removing methanol from the synthesis reaction liquid of compound A1, it is considered to have the properties of a blocky solid and a highly viscous substance, raising concerns about its difficulty in industrial manufacturing. In the manufacturing method described in Patent Document 2, compound A1 is synthesized using 2,6-dimethylphenol as a raw material through five steps: acetyl protection, bromination, methoxy substitution, Friedel-Crafts acylation, and dehydration condensation. These numerous reaction steps are unsuitable for large-scale industrial production. Furthermore, the properties of compound A1 obtained by crystallization with ethanol are unclear. In the isolation methods for crystallizing compound A1 described in Patent Documents 3 and 4, crystallization to the point of isolation requires 2 or 5 days, which can be understood as a significantly slow crystallization method, making it unsuitable for industrial production of compound A1. In view of the aforementioned problems discovered by the inventors, the object of this invention is to provide a method for rapidly performing crystallization in the crystallization step, suitable for large-scale industrial production, and efficient for manufacturing the crystals of compound A1. [Means for solving the problem]
[0005] In order to solve the above-mentioned problems, the inventors of this case conducted detailed research and found that by using a crystallization step with a specific solvent, crystallization proceeds rapidly. Due to the high yield, it is suitable for industrial production and can efficiently produce crystals of compound A1, thereby completing the present invention.
[0006] The present invention is as follows. 1. A method for producing crystals of a phenolic compound, wherein the phenolic compound is represented by chemical formula (A1) and has a methoxymethyl group, the method comprising a crystallization step, wherein crystals are precipitated from a solution containing a phenolic compound represented by chemical formula (A1) having a methoxymethyl group, a chain aliphatic alcohol solvent having 3 to 4 carbon atoms, and an aliphatic hydrocarbon solvent having 6 to 8 carbon atoms. 2. The method for producing crystals as described in 1., wherein the aforementioned chain aliphatic alcohol solvent having 3 to 4 carbon atoms is at least one selected from n-propanol, isopropanol, n-butanol, and isobutanol, and the aforementioned aliphatic hydrocarbon solvent having 6 to 8 carbon atoms is at least one selected from hexane, cyclohexane, octane, and isooctane. [Effects of the Invention]
[0007] The method for manufacturing crystals of a phenolic compound (compound A1) represented by chemical formula (A1) of the present invention, compared with the conventional method for manufacturing crystals of compound A1, has a faster crystal precipitation in the crystallization step. Due to its excellent yield, it is suitable for industrial manufacturing and can be manufactured efficiently.
Implementation Method
[0008] The present invention will be described in detail below. <Method for manufacturing crystals of a methoxymethyl phenol compound represented by chemical formula (A1) of the present invention> The method for manufacturing crystals of a methoxymethyl phenol compound (compound A1) represented by chemical formula (A1) of the present invention is characterized by including a crystallization step, which involves crystallization from a solution containing a methoxymethyl phenol compound represented by chemical formula (A1), a chain aliphatic alcohol solvent having 3 to 4 carbon atoms, and an aliphatic hydrocarbon solvent having 6 to 8 carbon atoms.
[0009] (A phenolic compound having a methoxymethyl group, represented by the chemical formula (A1)) In this invention, there are no particular limitations on the compound A1 provided as a raw material, nor on the method of synthesizing compound A1. It may also be a product obtained by isolation after the synthesis reaction. There are no particular limitations on the form, and examples include: solid, oil, block, and powder. Regarding compound A1, when analyzed by liquid chromatography using a UV detector with a wavelength of 280 nm, the detection area ratio of compound A1 relative to the detection area of all detected components is preferably in the range of 75.0% to 100% area, more preferably in the range of 80.0% to 100% area, even more preferably in the range of 83.0% to 100% area, and most preferably in the range of 85.0% to 100% area. Compound A1 may also contain a compound represented by chemical formula (A2) (sometimes referred to as "compound A2") or a compound represented by chemical formula (A3) (sometimes referred to as "compound A3") as its impurities. The compound represented by chemical formula (A2) is a dimer formed by the reaction of two molecules of compound A1 forming a methylene chain through the methoxymethyl groups of each other, and the compound represented by chemical formula (A3) is a trimer formed by three molecules of compound A1 similarly linked through methylene chains.
[0010] The synthesis method of compound A1 is illustrated by the following reaction formula. For example, a method for synthesizing a phenolic compound with chemical formula (A1) by reacting a phenolic compound with hydroxymethyl group (represented by chemical formula (B)) (hereinafter sometimes referred to as compound B) with methanol in the presence of an acid catalyst (hereinafter sometimes referred to as the "methoxylation method of hydroxymethyl group"). In the method for producing the crystallization of compound A1 of the present invention, the compound A1 provided as a raw material is preferably compound A1 synthesized by the "methoxylation method of hydroxymethyl group", which is synthesized by reacting a phenolic compound with hydroxymethyl group (represented by chemical formula (B)) with methanol in the presence of an acid catalyst. The method for producing compound A1 by the "methoxylation method of hydroxymethyl group" of the aforementioned synthesis method is described below. The synthesis method of the phenolic compound with hydroxymethyl group (represented by chemical formula (B)) (compound B) used in the aforementioned methoxylation method of hydroxymethyl group is not particularly limited, and can be synthesized by conventionally known methods. Examples of methods for synthesizing compound B include: reacting a triphenol compound (compound C) represented by chemical formula (C) with formaldehyde in the presence of an alkaline catalyst to synthesize a phenol compound (compound B) represented by chemical formula (B) having a hydroxymethyl group.
[0011] The amount of methanol used in the methoxylation method of hydroxymethyl of the present invention is preferably in the range of 80 to 170 mol relative to 1 mol of compound B, more preferably in the range of 100 to 150 mol, and particularly preferably in the range of 110 to 140 mol. This methanol can also function as a reaction solvent.
[0012] The acid catalyst used in the methoxylation method of hydroxymethyl groups according to the present invention can be specifically exemplified by, for example, sulfuric acid, hydrochloric acid, phosphoric acid, trifluoroacetic acid, trifluoromethanesulfonic acid, cation exchange resin (acidic form), oxalic acid, phosphotungstic acid, or silicottitic acid, etc., and preferably at least one of these compounds is used. Sulfuric acid is particularly preferred. The amount of acid catalyst used relative to 1 mole of compound B is preferably in the range of 0.5 to 2.5 moles, more preferably in the range of 1.0 to 2.0 moles, and particularly preferably in the range of 1.2 to 1.7 moles. The reaction temperature in the methoxylation method of hydroxymethyl groups according to the present invention is preferably in the range of 30 to 62°C, more preferably in the range of 45 to 62°C, and particularly preferably in the range of 58 to 62°C. After the reaction is completed, it is preferable to mix with an alkali such as sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, or potassium bicarbonate to neutralize the acid catalyst used in the reaction.
[0013] (Compound A1 after water washing) The compound A1 provided as a raw material is preferably compound A1 after water washing. This water washing is to remove water-soluble impurities (such as salts generated during the neutralization of acid catalysts) produced by the catalyst used in the synthesis reaction, the raw materials used, and the alkali used for neutralization. This water washing can be carried out by preparing a solution of compound A1 and an organic solvent in which compound A1 is dissolved and separated from water, and then washing its organic layer with water. Examples of compounds A1 suitable for water washing include: compound A1 contained in the reaction solution after the aforementioned synthesis reaction, and compound A1 obtained by prior isolation. When using a reaction solution containing compound A1 after the aforementioned synthesis reaction, the solvent is replaced with an organic solvent that can be used as an organic solvent to dissolve compound A1 and separate from water to prepare the solution. When using the previously extracted compound A1, it is mixed with an organic solvent that can be used as an organic solvent to dissolve compound A1 and separate it from water to prepare a solution. Examples of organic solvents that can be used as organic solvents to dissolve compound A1 and separate it from water include: aromatic hydrocarbon solvents with 7 to 9 carbon atoms such as toluene and xylene; chain aliphatic ketone solvents with a total of 4 to 8 carbon atoms such as methyl ethyl ketone, methyl isobutyl ketone, and methyl isopentyl ketone; and chain aliphatic carboxylic acid ester solvents with a total of 5 to 8 carbon atoms such as butyl acetate and amyl acetate. It is preferred to use at least one organic solvent selected from these. Preferably, at least one organic solvent is used, selected from chain aliphatic ketone solvents with a total of 4 to 8 carbon atoms and chain aliphatic carboxylic acid ester solvents with a total of 5 to 8 carbon atoms. More preferably, at least one organic solvent is used, selected from methyl ethyl ketone, methyl isobutyl ketone, methyl isopentyl ketone, butyl acetate, and amyl acetate. Most preferably, at least one organic solvent is used, selected from methyl ethyl ketone, methyl isobutyl ketone, butyl acetate, and amyl acetate. The amount of organic solvent used relative to compound A1 can be appropriately adjusted according to the solubility of compound A1 in the organic solvent used, preferably in the range of 0.5 to 5.0 times by weight, more preferably in the range of 0.5 to 4.0 times by weight, even more preferably in the range of 0.8 to 3.0 times by weight, and most preferably in the range of 0.8 to 2.0 times by weight. The amount of water used during the washing process can be adjusted appropriately according to the amount of water-soluble impurities to be removed. The water volume relative to the weight of the organic layer to be washed is preferably in the range of 0.5 to 3.0 times by weight, more preferably in the range of 0.5 to 2.5 times by weight, even more preferably in the range of 0.5 to 2.0 times by weight, and most preferably in the range of 0.5 to 1.5 times by weight. The number of times the organic layer is washed can be one or more times, depending on the amount of water-soluble impurities to be removed.
[0014] <Preparation of the solution used in the crystallization step of the present invention> Not limited to the methoxylation method of hydroxymethyl groups described above, a solution containing compound A1 synthesized by a known synthetic method can be prepared by replacing the solvent used in the reaction, such as methanol, with the organic solvent used in the crystallization step of the present invention. Furthermore, the compound A1 that has undergone water washing can be prepared by replacing the solvent with the organic solvent used in the crystallization step of the present invention, or by dissolving it in the organic solvent, to prepare a solution containing compound A1 and the organic solvent used in the crystallization step of the present invention. The method of replacing the solvent can be exemplified by the following: distilling off the organic solvent used in the reaction step to obtain a distillation residue containing compound A1, and then mixing it with the organic solvent used in the crystallization step of the present invention to prepare a solution containing compound A1 used in the crystallization step of the present invention; repeating the processes of "distilling off the organic solvent used in the reaction step from the reaction solution" and "mixing with the organic solvent used in the crystallization step of the present invention" to prevent the solution from drying out and maintain its solution state, and replacing the solvent with the organic solvent used in the crystallization step of the present invention to prepare a solution containing compound A1 used in the crystallization step of the present invention. Regarding the distillation conditions for removing the organic solvent, it is preferably carried out under heating, under reduced pressure, or under heating and reduced pressure, more preferably under heating and reduced pressure. The temperature is preferably in the range of 25 to 60°C, more preferably in the range of 25 to 55°C, and even more preferably in the range of 30 to 50°C. The pressure is preferably under reduced pressure, more preferably below 70 kPa, and even more preferably below 50 kPa. When preparing the solution containing compound A1 used in the crystallization step of the present invention, it is preferred to use the following method: prepare the solution by using compound A1 and a chain aliphatic alcohol solvent with 3 to 4 carbon atoms, and then add an aliphatic hydrocarbon solvent with 6 to 8 carbon atoms.
[0015] <Organic Solvent Used in Crystallization Step> The organic solvent used in the crystallization step of the present invention, namely a chain aliphatic alcohol solvent with 3 to 4 carbon atoms, can be specifically exemplified by: n-propanol, isopropanol (IPA), n-butanol, dibutanol, tributanol, isobutanol, etc. In the crystallization step of the present invention, it is preferable to use at least one solvent selected from n-propanol, isopropanol (IPA), n-butanol, dibutanol, tributanol, and isobutanol; more preferably, it is preferable to use at least one solvent selected from n-propanol, isopropanol (IPA), n-butanol, and isobutanol; even more preferably, it is preferable to use at least one solvent selected from isopropanol (IPA) and n-butanol; and most preferably, it is isopropanol (IPA). As an aliphatic hydrocarbon solvent with 6 to 8 carbon atoms used in the crystallization step of the present invention, it is preferably a chain aliphatic hydrocarbon solvent with 6 to 8 carbon atoms, more preferably a chain aliphatic hydrocarbon solvent with 6 or 8 carbon atoms, and even more preferably a chain aliphatic hydrocarbon solvent with 8 carbon atoms. Examples of aliphatic hydrocarbon solvents with 6 to 8 carbon atoms include hexane, cyclohexane, heptane, cycloheptane, octane, and cyclooctane. In the crystallization step of this invention, it is preferable to use at least one solvent selected from hexane, cyclohexane, heptane, cycloheptane, octane, and cyclooctane; more preferably, at least one solvent selected from n-hexane, cyclohexane, n-heptane, n-octane, and isooctane (2,2,4-trimethylpentane); even more preferably, at least one solvent selected from n-hexane, cyclohexane, n-octane, and isooctane; and most preferably, isooctane. In the crystallization step of this invention, a small amount of solvent other than the aforementioned organic solvents may be included, provided it does not impair the effects of this invention. "Small amount" refers to the amount of organic solvents and water used in steps such as the aforementioned reaction steps or water washing processes that remain therein after these removal steps have been performed.
[0016] In the crystallization step of the present invention, the amount of the 3- to 4-carbon chain aliphatic alcohol solvent used relative to compound A1 can be appropriately adjusted according to the solubility of compound A1 in the used 3- to 4-carbon chain aliphatic alcohol solvent, preferably in the range of 0.3 to 3.0 times by weight, more preferably in the range of 0.5 to 2.0 times by weight, even more preferably in the range of 0.5 to 1.5 times by weight, and most preferably in the range of 0.6 to 1.3 times by weight. The amount of the 3- to 4-carbon chain aliphatic alcohol solvent used can be adjusted by the amount added, or by removing it from the system by distillation. Furthermore, at the point of crystallization from the crystallization solution, relative to the total amount of the aliphatic alcohol solvent with 3 to 4 carbon atoms and the aliphatic hydrocarbon solvent with 6 to 8 carbon atoms used, the amount of the aliphatic alcohol solvent with 3 to 4 carbon atoms used is in the range of 0.5 to 0.95 times by weight, more preferably 0.5 to 0.9 times by weight, even more preferably 0.55 to 0.9 times by weight, and particularly preferably 0.55 to 0.8 times by weight. After crystallization, an aliphatic hydrocarbon solvent with 6 to 8 carbon atoms may be further added to the crystallization solution. In this case, ultimately, relative to the total amount of the aliphatic alcohol solvent with 3 to 4 carbon atoms and the aliphatic hydrocarbon solvent with 6 to 8 carbon atoms used, the amount of the aliphatic alcohol solvent with 3 to 4 carbon atoms used is preferably in the range of 0.1 to 0.5 times by weight, more preferably 0.1 to 0.4 times by weight.
[0017] (Conditions for the crystallization step) In this invention, the temperature for crystallization is preferably in the range of 5 to 45°C, more preferably in the range of 5 to 35°C, even more preferably in the range of 5 to 30°C, and most preferably in the range of 5 to 20°C. Seed crystals may not be used during crystallization, but it is preferable to use them. There are no restrictions on the type of crystal used as a seed crystal. The amount of seed crystal used is preferably in the range of 0.001 to 0.1 times the weight of the compound Al to be precipitated. After crystallization, from the viewpoint of yield, it is preferable to cool the crystallization solution. The cooling temperature is preferably in the range of 5 to 35°C, more preferably in the range of 5 to 30°C, and most preferably in the range of 5 to 20°C. There are no restrictions on the cooling rate of the crystallization solution, but it is preferably in the range of 3 to 15°C / h.
[0018] <Subsequent Steps of the Crystallization Step> The crystals of compound A1 obtained by the crystallization step in the aforementioned manufacturing method can be separated and recovered from the crystallization solution by filtration. In this invention, it is preferable to further include a filtration step to filter out the crystals precipitated in the aforementioned crystallization step. During filtration, an organic solvent, such as the solvent used in the crystallization step, can be used to clean the filtered crystals. The filtered crystals can be dried to remove the solvent used. In this invention, it is preferable to further include a drying step to dry the crystals filtered in the aforementioned filtration step. The drying step is preferably carried out at a temperature in the range of 25 to 50°C, more preferably in the range of 25 to 45°C, and even more preferably in the range of 25 to 40°C. The pressure during drying can be atmospheric pressure or reduced pressure; in industrial applications, it is preferable to use reduced pressure. Specifically, it is preferable to use a reduced pressure of 10 kPa or less, and even more preferably to use a reduced pressure of 5 kPa or less. Furthermore, in order to suppress oxidation, deterioration, and discoloration caused by oxygen, the above-described steps of reaction, neutralization, washing, crystallization, filtration, distillation, drying, packaging, melting, and cooling in this invention are preferably carried out in an inert gas environment such as nitrogen or argon, or in an environment with a lower oxygen level than air. [Example]
[0019] The present invention will be specifically described below by way of examples and comparative examples, but the present invention is not limited to these examples and comparative examples. <Analytical Method> 1. High-speed liquid chromatography (HPLC) analysis The contents of impurities such as compound A1, compound A2, and compound A3 in the examples were calculated from the area ratio of the high-speed liquid chromatography (HPLC) chromatograms measured under the following conditions. Apparatus: Prominence, manufactured by Shimadzu Corporation; Pump: LC-20AT; Column oven: CTO-20A; Detector: SPD-20A; Column: Shim-Pack CLC-ODS (inner diameter 6mm, length 150mm); Oven temperature: 50℃; Flow rate: 1mL / min; Mobile phase: (A) 0.2 vol% acetic acid aqueous solution, (B) methanol gradient conditions: (B) vol% 0-30min, 50%→100% 30-45min, 100%; Sample injection volume: 20μL; Detection wavelength: 280nm. 2. Differential scanning calorimetry (DSC): Crystallized material was precisely weighed into an aluminum pot. Using a differential scanning calorimetry apparatus (Hitachi High-Tech Science Co., Ltd.: DSC7020), with an empty aluminum pot as a control, the determination was performed under the following operating conditions. (Operating Conditions) Heating rate: 10℃ / min. Measurement temperature range: 30 to 400℃. Measurement environment: Nitrogen gas 50 mL / min. Sample volume: 4 to 5 mg
[0020] <Example 1> 1731 g (54.11 mol) of methanol and 57.7 g (0.59 mol) of sulfuric acid were added to a 5 L four-necked flask equipped with a stirrer, thermometer, and cooler, and the mixture was heated to 60 °C. 192.4 g (0.40 mol) of a phenolic compound with hydroxymethyl group (represented by chemical formula (B)) was added, and the mixture was stirred at 60 °C for 6 hours. The reaction solution was then cooled, and an aqueous solution of sodium hydroxide and phosphoric acid was added for neutralization. Methanol was removed by distillation under reduced pressure, and 462.0 g of water and 462.0 g of butyl acetate were added and stirred. The mixture was allowed to stand for 30 minutes, and the aqueous layer was removed. The organic layer was then washed with water several times to obtain 816 g of a cleaned organic layer containing compound A1. The HPLC analysis of the obtained organic layer by the above method showed that compound A1 accounted for 86.9% of the area, compound A2 accounted for 5.6% of the area, and compound A3 accounted for 0.6% of the area. A portion (263g) of the cleaned organic layer containing compound A1 was transferred to a four-necked flask equipped with a stirrer, thermometer, and cooler. The solvent in 177g of the organic layer was removed by distillation under reduced pressure, yielding a distillation residue. HPLC analysis of the distillation residue using the above method showed that compound A1 had an area percentage of 86.9%, compound A2 5.6%, and compound A3 0.6%. To prepare a crystallization solution of compound A1 with the aforementioned composition, 54.4g of isopropanol (IPA) was added to the distillation residue and dissolved. Then, 22.0g of isooctane was added, and the solution was cooled to 30°C (at this point, the weight of IPA in the crystallization solution was 0.7 times the total weight of IPA and isooctane; this is recorded as "0.7 times the weight of crystallization solution" in Figure 1). 1.4g of crystals of compound A1 were added as seed crystals, and the solution was cooled to 15°C over 1 hour. The solution was then stirred at 15°C for 20.5 hours, resulting in crystal precipitation. Next, 44.5 g of isooctane was mixed and stirred at 15°C for 21 hours (at this point, the weight of IPA in the crystallization solution was 0.4 times the total weight of IPA and isooctane; this is recorded as "0.4 times the weight of crystallization solution" in Figure 1). Then, 120 g of isooctane was mixed and stirred at 15°C for 17 hours (at this point, the amount of IPA in the crystallization solution was 0.2 times the total weight of IPA and isooctane; this is recorded as "0.2 times the weight of crystallization solution" in Figure 1). During the above crystallization steps, the supernatant was sampled, and the concentration of compound A1 in the supernatant was analyzed by liquid chromatography to confirm the change in concentration over time. The results are shown in Figure 1. These results confirm that in the "0.7 times the weight of crystallization solution", the concentration of compound A1 in the supernatant of the crystallization solution gradually decreased during the continuous crystallization operation. This is presumably due to the growth of crystals, indicating rapid crystallization.It was found that the concentration of compound A1 decreased with the addition of isooctane, leading to further crystallization. The precipitated crystals were filtered and dried, yielding 63.2 g of compound A1 crystals (yield 86.9%). HPLC analysis of the obtained compound A1 crystals was performed using the above method, resulting in an area percentage of 87.2% for compound A1, 5.7% for compound A2, and 0.7% for compound A3. Differential scanning calorimetry (DSC) analysis of the obtained compound A1 crystals showed an onset temperature of 55.9 °C, an endothermic peak temperature of 68.2 °C, and a heat of fusion based on the observed endothermic peak of 77.0 mJ / mg. The DSC analysis results are shown in Figure 2.
[0021] <Example 2> 456.1 g (14.25 mol) of methanol and 15.3 g (0.16 mol) of sulfuric acid were added to a 1 L four-necked flask equipped with a stirrer, thermometer, and cooler, and the mixture was heated to 60 °C. 50.8 g (0.1 mol) of compound B was added, and the mixture was stirred at 60 °C for 8 hours. The reaction mixture was then cooled, and an aqueous solution of sodium hydroxide and phosphoric acid was added for neutralization. Methanol was removed by distillation under reduced pressure. 114.4 g of water and 114.4 g of butyl acetate were added and stirred. The mixture was allowed to stand for 30 minutes, and the aqueous layer was removed. The organic layer was then washed with water several times to obtain a cleaned organic layer containing compound A1. 106.8 g of the solvent from the organic layer was distilled off from the flask by distillation under reduced pressure to obtain a distillation residue. The HPLC analysis of the distillation residue obtained by the above method showed that compound A1 had an area percentage of 86.6%, compound A2 had an area percentage of 6.3%, and compound A3 had an area percentage of 0.7%. To prepare a crystallization solution of compound A1 with the aforementioned composition, 31.5 g of IPA was added to the obtained distillation residue and heated to 47°C to dissolve it. Then, 22.0 g of isooctane was added, and the solution was cooled to 30°C (at this point, the weight of IPA in the crystallization solution was 0.59 times the total weight of IPA and isooctane). 0.9 g of crystals of compound A1 were added as seed crystals, and the solution was cooled to 15°C over 1.5 hours. Then, 103.9 g of isooctane was added dropwise over 2.5 hours, and the solution was stirred for 18 hours (at this point, the weight of IPA in the crystallization solution was 0.14 times the total weight of IPA and isooctane). The precipitated crystals were filtered and dried to obtain 48.9 g of crystals of compound A1 (yield 82.2%). The crystals of compound A1 obtained using the above method were analyzed by HPLC. The results showed that compound A1 had an area of 86.9%, compound A2 had an area of 6.2%, and compound A3 had an area of 0.7%. The crystals of compound A1 obtained by DSC analysis showed an initial temperature of 55.0℃, a peak temperature of 68.1℃ for the endothermic peak, and a heat of fusion based on the observed endothermic peak of 73.2 mJ / mg. The DSC analysis results are shown in Figure 3.
[0022] <Example 3> 2883 g (90.1 mol) of methanol and 96.1 g (0.98 mol) of sulfuric acid were added to a 5 L four-necked flask equipped with a stirrer, thermometer, and cooler, and the mixture was heated to 60 °C. 320.3 g (0.66 mol) of compound B was added, and the mixture was stirred at 60 °C for 6 hours. The reaction mixture was then cooled, and an aqueous solution of sodium hydroxide and phosphoric acid was added for neutralization. Methanol was removed by distillation under reduced pressure. 762.5 g of water and 833.3 g of butyl acetate were added and stirred. The mixture was allowed to stand for 30 minutes, and the aqueous layer was removed. The organic layer was then washed with water several times to obtain a cleaned organic layer containing compound A1. 790.9 g of the solvent from the organic layer was distilled off from the flask by distillation under reduced pressure to obtain a distillation residue. The HPLC analysis of the distillation residue obtained by the above method showed that compound A1 had an area percentage of 86.4%, compound A2 had an area percentage of 6.2%, and compound A3 had an area percentage of 0.7%. To prepare a crystallization solution of compound A1 with the aforementioned composition, 214.6 g of IPA was added to the distillation residue at 47°C and dissolved. Then, 142.9 g of isooctane was added, and the solution was cooled to 30°C (at this point, the weight of IPA in the crystallization solution was 0.60 times the total weight of IPA and isooctane). 6.4 g of crystals of compound A1 were added as seed crystals, and the solution was cooled to 15°C over 3 hours. Then, 711.7 g of isooctane was added dropwise over 1 hour, and the solution was stirred for 18 hours (at this point, the weight of IPA in the crystallization solution was 0.20 times the total weight of IPA and isooctane). The precipitated crystals were filtered and dried to obtain 311.4 g of crystals of compound A1 (yield 82.9%). The crystals of compound A1 obtained using the above method were analyzed by HPLC. The results showed that compound A1 had an area of 86.5%, compound A2 had an area of 6.3%, and compound A3 had an area of 0.8%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed an initial temperature of 51.8℃, a peak temperature of 68.1℃ for the endothermic peak, and a heat of fusion based on the observed endothermic peak of 67.4 mJ / mg. The DSC analysis results are shown in Figure 4.
[0023] <Example 4> In a 1L four-necked flask equipped with a stirrer, thermometer, and cooler, 336.6g (10.50mol) of methanol and 11.2g (0.11mol) of sulfuric acid were added and heated to 60°C. 39.0g (0.08mol) of a phenolic compound containing hydroxymethyl groups (represented by chemical formula (B)) was added, and the mixture was stirred at 60°C for 6 hours. The reaction mixture was then cooled, and an aqueous solution of sodium hydroxide and phosphoric acid was added for neutralization. Methanol was removed by distillation under reduced pressure (temperature range of 30 to 50°C, pressure range of less than 50 kPa). 89.8g of water and 89.8g of butyl acetate were added and stirred. The mixture was allowed to stand for 30 minutes, and the aqueous layer was removed. The organic layer was then washed with water several times to obtain 127g of a cleaned organic layer containing compound A1. The obtained organic layer, analyzed by HPLC using the above method, showed that compound A1 had an area of 86.4%, compound A2 had an area of 5.6%, and compound A3 had an area of 0.6%. The organic layer containing compound A1 was subjected to distillation under reduced pressure to remove the solvent from 84.2 g of the organic layer, yielding a distillation residue. The distillation residue, analyzed by HPLC using the above method, showed that compound A1 had an area of 86.4%, compound A2 had an area of 5.6%, and compound A3 had an area of 0.6%. To prepare a crystallization solution containing compound A1, 30.1 g of isopropanol (IPA) was added to the distillation residue at 47°C and dissolved. 5.05 g of the resulting IPA solution was transferred to a 100 mL test tube, and 1.49 g of octane was added. The solution was stirred with a stir bar while cooling to 30°C (at this point, the weight of IPA in the crystallization solution was 0.60 times the weight of the total weight of IPA and octane). 0.0586 g of crystals of compound A1 were added as seed crystals, and the mixture was cooled to 20°C over 1 hour. Then, 7.39 g of octane was added dropwise over 1 hour, and the mixture was cooled to 7°C over 2 hours. The mixture was then stirred for 16 hours (at this point, the weight of IPA in the crystallization solution was 0.20 times the total weight of IPA and octane). The precipitated crystals were filtered and dried to obtain 2.38 g of crystals of compound A1 (yield 73.0%). HPLC analysis of the obtained crystals of compound A1 using the above method showed that compound A1 had an area percentage of 87.2%, compound A2 had an area percentage of 6.4%, and compound A3 had an area percentage of 0.9%. Differential scanning calorimetry (DSC) analysis of the obtained crystals of compound A1 showed an initial temperature of 57.2°C, a peak temperature of 68.4°C for the endothermic peak, and a heat of fusion based on the observed endothermic peak of 71.1 mJ / mg.
[0024] <Example 5> Take 4.98 g of the IPA solution containing compound A1 obtained in Example 4 into a 100 mL test tube, add 1.51 g of hexane, and cool to 30°C while stirring with a stir bar (at this point, the weight of IPA in the crystallization solution is 0.60 times the total weight of IPA and hexane). Add 0.0549 g of crystals of compound A1 as seed crystals, and cool to 20°C for 1 hour. Then, add 7.39 g of hexane dropwise over 1 hour, and cool to 7°C for 2 hours. Then, stir for 16 hours (at this point, the weight of IPA in the crystallization solution is 0.20 times the total weight of IPA and hexane). Filter out the precipitated crystals and dry them to obtain 2.33 g of crystals of compound A1 (yield 72.5%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 87.4%, compound A2 had an area of 6.2%, and compound A3 had an area of 0.8%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 56.4℃, the peak temperature of the endothermic peak was 68.7℃, and the heat of fusion based on the observed endothermic peak was 68.8 mJ / mg.
[0025] <Example 6> Take 5.00 g to 100 mL of the IPA solution containing compound A1 obtained in Example 4, add 1.48 g of cyclohexane, and cool to 30°C while stirring with a stir bar (at this point, the weight of IPA in the crystallization solution is 0.60 times the total weight of IPA and cyclohexane). Add 0.0545 g of crystals of compound A1 as seed crystals, and cool to 10°C for 2 hours. Then, add 7.37 g of cyclohexane dropwise over 1 hour, and cool to 7°C for 0.5 hours. Then, add 11.07 g of cyclohexane dropwise over 1 hour, and stir for 16 hours (at this point, the weight of IPA in the crystallization solution is 0.10 times the total weight of IPA and cyclohexane). Filter out the precipitated crystals and dry them to obtain 2.06 g of crystals of compound A1 (yield 63.8%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 88.5%, compound A2 had an area of 5.4%, and compound A3 had an area of 0.8%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 61.4℃, the peak temperature of the endothermic peak was 70.2℃, and the heat of fusion was 70.7 mJ / mg.
[0026] <Example 7> In a 1L four-necked flask equipped with a stirrer, thermometer, and cooler, 336.6g (10.50mol) of methanol and 11.2g (0.11mol) of sulfuric acid were added and heated to 60°C. 39.0g (0.08mol) of a phenolic compound containing hydroxymethyl groups (represented by chemical formula (B)) was added, and the mixture was stirred at 60°C for 6 hours. The reaction mixture was then cooled, and an aqueous solution of sodium hydroxide and phosphoric acid was added for neutralization. Methanol was removed by distillation under reduced pressure (temperature range of 30 to 50°C, pressure range of less than 50 kPa). 89.8g of water and 89.8g of butyl acetate were added and stirred. The mixture was allowed to stand for 30 minutes, and the aqueous layer was removed. The organic layer was then washed with water several times to obtain 127g of a washed organic layer containing compound A1. The obtained organic layer, analyzed by HPLC using the above method, showed that compound A1 had an area of 86.4%, compound A2 had an area of 5.6%, and compound A3 had an area of 0.6%. The organic layer containing compound A1 was subjected to distillation under reduced pressure to remove the solvent from 84.2 g of the organic layer, yielding a distillation residue. The distillation residue, analyzed by HPLC using the above method, showed that compound A1 had an area of 86.4%, compound A2 had an area of 5.6%, and compound A3 had an area of 0.6%. To prepare the crystallization solution containing compound A1, 30.1 g of n-propanol was added to the distillation residue at 47°C and dissolved. From this n-propanol solution, 5.00 g to 100 mL of the solution was transferred to a test tube, and 1.49 g of isooctane was added. The solution was stirred with a stir bar while cooling to 30°C (at this point, the weight of n-propanol in the crystallization solution was 0.60 times the total weight of n-propanol and isooctane). 0.0580 g of crystals of compound A1 were added as seed crystals, and the mixture was cooled to 20°C over 1 hour. Then, 7.85 g of isooctane was added dropwise over 1 hour, and the mixture was cooled to 7°C over 2 hours. The mixture was then stirred for 16 hours (at this point, the weight of n-propanol in the crystallization solution was 0.20 times the total weight of n-propanol and isooctane). The precipitated crystals were filtered and dried to obtain 1.89 g of crystals of compound A1 (yield 58.4%). HPLC analysis of the obtained crystals of compound A1 using the above method showed that compound A1 had an area percentage of 88.4%, compound A2 had an area percentage of 5.6%, and compound A3 had an area percentage of 1.0%. Differential scanning calorimetry (DSC) analysis of the obtained crystals of compound A1 showed an initial temperature of 58.5°C, a peak temperature of 68.7°C for the endothermic peak, and a heat of fusion of 74.3 mJ / mg.
[0027] <Example 8> Take 5.08 g of the n-propanol solution containing compound A1 obtained in Example 7 into a 100 mL test tube, add 1.52 g of octane, and cool to 30°C while stirring with a stir bar (at this time, the weight of n-propanol in the crystallization solution is 0.60 times the total weight of n-propanol and octane). Add 0.0599 g of crystals of compound A1 as seed crystals, and cool to 20°C for 1 hour. Then, add 7.60 g of octane dropwise over 1 hour, and cool to 7°C for 2 hours. Then stir for 16 hours (at this time, the weight of n-propanol in the crystallization solution is 0.20 times the total weight of n-propanol and octane). Filter out the precipitated crystals and dry them to obtain 2.34 g of crystals of compound A1 (yield 71.7%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 87.9%, compound A2 had an area of 6.0%, and compound A3 had an area of 0.9%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 59.4℃, the peak temperature of the endothermic peak was 68.6℃, and the heat of fusion based on the observed endothermic peak was 64.4 mJ / mg.
[0028] <Example 9> Take 5.00 g to 100 mL of the n-propanol solution containing compound A1 obtained in Example 7, add 1.49 g of hexane, and cool to 30°C while stirring with a stir bar (at this time, the weight of n-propanol in the crystallization solution is 0.60 times the total weight of n-propanol and hexane). Add 0.0550 g of crystals of compound A1 as seed crystals, and cool to 20°C for 1 hour. Then, add 7.55 g of hexane dropwise over 1 hour, and cool to 7°C for 2 hours. Then, stir for 16 hours (at this time, the weight of n-propanol in the crystallization solution is 0.20 times the total weight of n-propanol and hexane). Filter out the precipitated crystals and dry them to obtain 2.00 g of crystals of compound A1 (yield 61.8%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 87.8%, compound A2 had an area of 6.1%, and compound A3 had an area of 0.9%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 53.8℃, the peak temperature of the endothermic peak was 68.5℃, and the heat of fusion was 69.2 mJ / mg.
[0029] <Example 10> Take 5.55 g of the n-propanol solution containing compound A1 obtained in Example 7 into a 100 mL test tube, add 1.66 g of cyclohexane, and cool to 30°C while stirring with a stir bar (at this time, the weight of n-propanol in the crystallization solution is 0.60 times the total weight of n-propanol and cyclohexane). Add 0.0594 g of crystals of compound A1 as seed crystals, and cool to 15°C over 1.5 hours. Then, add 8.38 g of cyclohexane dropwise over 1 hour. Then, cool to 7°C over 1.5 hours and stir for 16 hours (at this time, the weight of n-propanol in the crystallization solution is 0.20 times the total weight of n-propanol and cyclohexane). Filter out the precipitated crystals and dry them to obtain 1.32 g of crystals of compound A1 (yield 36.7%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 92.8%, compound A2 had an area of 3.2%, and compound A3 had an area of 0.4%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 64.6℃, the peak temperature of the endothermic peak was 71.7℃, and the heat of fusion was 81.4 mJ / mg.
[0030] <Example 11> In a 1L four-necked flask equipped with a stirrer, thermometer, and cooler, 336.6g (10.50mol) of methanol and 11.2g (0.11mol) of sulfuric acid were added and heated to 60°C. 39.0g (0.08mol) of a phenolic compound containing hydroxymethyl groups (represented by chemical formula (B)) was added, and the mixture was stirred at 60°C for 6 hours. The reaction mixture was then cooled, and an aqueous solution of sodium hydroxide and phosphoric acid was added for neutralization. Methanol was removed by distillation under reduced pressure (temperature range of 30 to 50°C, pressure range of less than 50 kPa). 89.8g of water and 89.8g of butyl acetate were added and stirred. The mixture was allowed to stand for 30 minutes, and the aqueous layer was removed. The organic layer was then washed with water several times to obtain 127g of a washed organic layer containing compound A1. The obtained organic layer, analyzed by HPLC using the above method, showed that compound A1 had an area of 86.4%, compound A2 had an area of 5.6%, and compound A3 had an area of 0.6%. The organic layer containing compound A1 was subjected to distillation under reduced pressure to remove 84.2 g of solvent, yielding a distillation residue. The distillation residue, analyzed by HPLC using the above method, showed that compound A1 had an area of 86.4%, compound A2 had an area of 5.6%, and compound A3 had an area of 0.6%. To prepare the crystallization solution containing compound A1, 30.1 g of n-butanol was added to the distillation residue at 47°C and dissolved. 5.05 g of the resulting n-butanol solution was transferred to a 100 mL test tube, and 1.50 g of isooctane was added. The solution was stirred with a stir bar while cooling to 30°C (at this point, the weight of n-butanol in the crystallization solution was 0.60 times the total weight of n-butanol and isooctane). 0.0573 g of crystallized compound A1 was added as a seed crystal, and the mixture was cooled to 20°C over 1 hour. Then, 7.50 g of isooctane was added dropwise over 1 hour, and the mixture was cooled to 7°C over 2 hours. The mixture was then stirred for 16 hours (at this point, the weight of n-butanol in the crystallization solution was 0.20 times the total weight of n-butanol and isooctane). The precipitated crystals were filtered and dried to obtain 2.46 g of crystallized compound A1 (yield 75.0%). HPLC analysis of the obtained crystallized compound A1 using the above method showed that compound A1 had an area percentage of 87.5%, compound A2 had an area percentage of 6.2%, and compound A3 had an area percentage of 0.9%. Differential scanning calorimetry (DSC) analysis of the obtained crystallized compound A1 showed an initial temperature of 57.2°C, a peak temperature of 67.3°C for the endothermic peak, and a heat of fusion of 71.2 mJ / mg.
[0031] <Example 12> Take 5.05 g of the n-butanol solution containing compound A1 obtained in Example 11 into a 100 mL test tube, add 1.48 g of octane, and cool to 30°C while stirring with a stir bar (at this time, the weight of n-butanol in the crystallization solution is 0.60 times the total weight of n-butanol and octane). Add 0.0558 g of crystals of compound A1 as seed crystals, and cool to 20°C for 1 hour. Then, add 7.52 g of octane dropwise over 1 hour, and cool to 7°C over 2 hours. Then stir for 16 hours (at this time, the weight of n-butanol in the crystallization solution is 0.20 times the total weight of n-butanol and octane). Filter out the precipitated crystals and dry them to obtain 2.31 g of crystals of compound A1 (yield 70.4%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 87.7%, compound A2 had an area of 6.1%, and compound A3 had an area of 0.8%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 58.1℃, the peak temperature of the endothermic peak was 67.6℃, and the heat of fusion was 70.9 mJ / mg.
[0032] <Example 13> Take 5.03 g of the n-butanol solution containing compound A1 obtained in Example 11 into a 100 mL test tube, add 1.55 g of hexane, and cool to 30°C while stirring with a stir bar (at this time, the weight of n-butanol in the crystallization solution is 0.60 times the total weight of n-butanol and hexane). Add 0.0554 g of crystals of compound A1 as seed crystals, and cool to 20°C for 1 hour. Then, add 7.48 g of hexane dropwise over 1 hour, and cool to 7°C over 2 hours. Then stir for 16 hours (at this time, the weight of n-butanol in the crystallization solution is 0.20 times the total weight of n-butanol and hexane). Filter out the precipitated crystals and dry them to obtain 2.39 g of crystals of compound A1 (yield 73.1%). The crystals of the obtained compound A1 were analyzed by HPLC using the above method. The area percentages were 88.3% for compound A1, 5.7% for compound A2, and 0.8% for compound A3. The crystals of the obtained compound A1 were analyzed by differential scanning calorimetry (DSC). The initial temperature was 57.5℃, the peak temperature of the endothermic peak was 68.8℃, and the heat of fusion was 72.2 mJ / mg.
[0033] <Example 14> Take 5.03 g of the n-butanol solution containing compound A1 obtained in Example 11 into a 100 mL test tube, add 1.51 g of cyclohexane, and cool to 30°C while stirring with a stir bar (at this time, the weight of n-butanol in the crystallization solution is 0.60 times the total weight of n-butanol and cyclohexane). Add 0.0558 g of crystals of compound A1 as seed crystals, and cool to 10°C for 2 hours. Then, add 7.56 g of cyclohexane dropwise over 1 hour, and cool to 7°C over 0.5 hours. Then, add 11.00 g of cyclohexane dropwise over 1 hour, and stir for 16 hours (at this time, the weight of n-butanol in the crystallization solution is 0.10 times the total weight of n-butanol and cyclohexane). Filter out the precipitated crystals and dry them to obtain 2.05 g of crystals of compound A1 (yield 62.7%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 88.9%, compound A2 had an area of 5.2%, and compound A3 had an area of 0.9%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 60.6℃, the peak temperature of the endothermic peak was 69.7℃, and the heat of fusion was 71.6 mJ / mg.
[0034] <Example 15> 336.6 g (10.50 mol) of methanol and 11.2 g (0.11 mol) of sulfuric acid were added to a 1 L four-necked flask equipped with a stirrer, thermometer, and cooler, and the mixture was heated to 60 °C. 39.0 g (0.08 mol) of a phenolic compound containing hydroxymethyl group (represented by chemical formula (B)) was added, and the mixture was stirred at 60 °C for 6 hours. The reaction solution was then cooled, and an aqueous solution of sodium hydroxide and phosphoric acid was added for neutralization. Methanol was removed by distillation under reduced pressure (temperature range of 30 to 50 °C, pressure range of less than 50 kPa). 89.8 g of water and 89.8 g of butyl acetate were added and stirred. The mixture was allowed to stand for 30 minutes, and the aqueous layer was removed. The organic layer was then washed with water several times to obtain 127 g of a cleaned organic layer containing compound A1. The obtained organic layer, analyzed by HPLC using the above method, showed that compound A1 had an area of 86.4%, compound A2 had an area of 5.6%, and compound A3 had an area of 0.6%. The organic layer containing compound A1 was subjected to distillation under reduced pressure to remove the solvent from 84.2 g of the organic layer, yielding a distillation residue. The distillation residue, analyzed by HPLC using the above method, showed that compound A1 had an area of 86.4%, compound A2 had an area of 5.6%, and compound A3 had an area of 0.6%. To prepare the crystallization solution containing compound A1, 30.1 g of isobutanol was added to the distillation residue at 47°C to dissolve it. 5.06 g of the isobutanol solution containing compound A1 was transferred to a 100 mL test tube, and 1.60 g of isooctane was added. The solution was stirred with a stir bar while cooling to 30°C (at this point, the weight of isobutanol in the crystallization solution was 0.60 times the total weight of isobutanol and isooctane). 0.0569 g of crystals of compound A1 were added as seed crystals, and the mixture was cooled to 20°C over 1 hour. Then, 7.40 g of isooctane was added dropwise over 1 hour, and the mixture was cooled to 7°C over 2 hours. The mixture was then stirred for 16 hours (at this point, the weight of isobutanol in the crystallization solution was 0.20 times the total weight of isobutanol and isooctane). The precipitated crystals were filtered and dried to obtain 2.36 g of crystals of compound A1 (yield 72.6%). HPLC analysis of the obtained crystals of compound A1 using the above method showed that compound A1 had an area percentage of 87.0%, compound A2 had an area percentage of 6.5%, and compound A3 had an area percentage of 0.9%. Differential scanning calorimetry (DSC) analysis of the obtained crystals of compound A1 showed an initial temperature of 53.9°C, a peak temperature of 67.1°C for the endothermic peak, and a heat of fusion of 67.8 mJ / mg.
[0035] <Example 16> Take 5.02 g of the isobutanol solution containing compound A1 obtained in Example 15 into a 100 mL test tube, add 1.47 g of octane, and cool to 30°C while stirring with a stir bar (at this time, the weight of isobutanol in the crystallization solution is 0.60 times the total weight of isobutanol and octane). Add 0.0554 g of crystals of compound A1 as seed crystals, and cool to 20°C for 1 hour. Then, add 7.31 g of octane dropwise over 1 hour, and cool to 7°C for 2 hours. Then, stir for 16 hours (at this time, the weight of isobutanol in the crystallization solution is 0.20 times the total weight of isobutanol and octane). Filter out the precipitated crystals and dry them to obtain 2.33 g of crystals of compound A1 (yield 72.2%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 87.2%, compound A2 had an area of 6.3%, and compound A3 had an area of 0.9%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 53.6℃, the peak temperature of the endothermic peak was 67.9℃, and the heat of fusion was 64.5 mJ / mg.
[0036] <Example 17> Take 5.01 g of the isobutanol solution containing compound A1 obtained in Example 15 into a 100 mL test tube, add 1.50 g of hexane, and cool to 30°C while stirring with a stir bar (at this time, the weight of isobutanol in the crystallization solution is 0.60 times the total weight of isobutanol and hexane). Add 0.0551 g of the crystals of compound A1 as seed crystals, and cool to 20°C for 1 hour. Then, add 7.38 g of hexane dropwise over 1 hour, and cool to 7°C for 2 hours. Then, stir for 16 hours (at this time, the weight of isobutanol in the crystallization solution is 0.20 times the total weight of isobutanol and hexane). Filter out the precipitated crystals and dry them to obtain 2.08 g of crystals of compound A1 (yield 64.6%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 87.5%, compound A2 had an area of 6.1%, and compound A3 had an area of 0.9%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 55.3℃, the peak temperature of the endothermic peak was 68.1℃, and the heat of fusion was 67.8 mJ / mg.
[0037] <Example 18> Take 5.03 g of the isobutanol solution containing compound A1 obtained in Example 15 into a 100 mL test tube, add 1.46 g of cyclohexane, and cool to 30°C while stirring with a stir bar (at this time, the weight of isobutanol in the crystallization solution is 0.60 times the total weight of isobutanol and cyclohexane). Add 0.0550 g of crystals of compound A1 as seed crystals, and cool to 15°C over 1.5 hours. Then, add 7.39 g of cyclohexane dropwise over 1 hour, and cool to 7°C over 1.5 hours. Then, stir for 16 hours (at this time, the weight of isobutanol in the crystallization solution is 0.10 times the total weight of isobutanol and cyclohexane). Filter out the precipitated crystals and dry them to obtain 1.80 g of crystals of compound A1 (yield 55.7%). The crystals of compound A1 obtained by the above method were analyzed by HPLC. The results showed that compound A1 had an area of 91.1%, compound A2 had an area of 4.1%, and compound A3 had an area of 0.6%. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed that the initial temperature was 63.2℃, the peak temperature of the endothermic peak was 70.9℃, and the heat of fusion was 73.8 mJ / mg.
[0038] The HPLC analysis results of the crystallization solution and the obtained crystals in Examples 1 to 18 above, as well as the DSC analysis results and yields of the obtained crystals, are shown in Tables 1 to 4.
[0039] [Table 1] Experimental Example Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Types of good solvents IPA IPA IPA IPA IPA IPA Undesirable solvent types Isooctane Isooctane Isooctane Octane hexane Cyclohexane Analysis object Analytical methods Measured values crystallization solution HPLC Compound A1 (area%) 86.9 86.6 86.4 86.4 86.4 86.4 Compound A2 (area%) 5.6 6.3 6.2 5.6 5.6 5.6 Compound A3 (area%) 0.6 0.7 0.7 0.6 0.6 0.6 Compound A crystallization HPLC Compound A1 (area%) 87.2 86.9 86.5 87.2 87.4 88.5 Compound A2 (area%) 5.7 6.2 6.3 6.4 6.2 5.4 Compound A3 (area%) 0.7 0.7 0.8 0.9 0.8 0.8 DSC Starting temperature (°C) 55.9 55.0 51.8 57.2 56.4 61.4 Peak temperature (°C) 68.2 68.1 68.1 68.4 68.7 70.2 Heat of fusion (mJ / mg) 77.0 73.2 67.4 71.1 68.8 70.7 Yield 86.9 82.2 82.9 73.0 72.5 63.8
[0040] [Table 2] Experimental Example Example 7 Example 8 Example 9 Example 10 Types of good solvents n-Propanol n-Propanol n-Propanol n-Propanol Undesirable solvent types Isooctane Octane hexane Cyclohexane Analysis object Analytical methods Measured values crystallization solution HPLC Compound A1 (area%) 86.4 86.4 86.4 86.4 Compound A2 (area%) 5.6 5.6 5.6 5.6 Compound A3 (area%) 0.6 0.6 0.6 0.6 Compound A crystallization HPLC Compound A1 (area%) 88.4 87.9 87.8 92.8 Compound A2 (area%) 5.6 6.0 6.1 3.2 Compound A3 (area%) 1.0 0.9 0.9 0.4 DSC Starting temperature (°C) 58.5 59.4 53.8 64.6 Peak temperature (°C) 68.7 68.6 68.5 71.7 Heat of fusion (mJ / mg) 74.3 64.4 69.2 81.4 Yield 58.4 71.7 61.8 36.7
[0041] [Table 3] Experimental Example Example 11 Example 12 Example 13 Example 14 Types of good solvents n-Butanol n-Butanol n-Butanol n-Butanol Undesirable solvent types Isooctane Octane hexane Cyclohexane Analysis object Analytical methods Measured values crystallization solution HPLC Compound A1 (area%) 86.4 86.4 86.4 86.4 Compound A2 (area%) 5.6 5.6 5.6 5.6 Compound A3 (area%) 0.6 0.6 0.6 0.6 Compound A crystallization HPLC Compound A1 (area%) 87.5 87.7 88.3 88.9 Compound A2 (area%) 6.2 6.1 5.7 5.2 Compound A3 (area%) 0.9 0.8 0.8 0.9 DSC Starting temperature (°C) 57.2 58.1 57.5 60.6 Peak temperature (°C) 67.3 67.6 68.8 69.7 Heat of fusion (mJ / mg) 71.2 70.9 72.2 71.6 Yield 75.0 70.4 73.1 62.7
[0042] [Table 4] Experimental Example Example 15 Example 16 Example 17 Example 18 Types of good solvents Isobutanol Isobutanol Isobutanol Isobutanol Undesirable solvent types Isooctane Octane hexane Cyclohexane Analysis object Analytical methods Measured values crystallization solution HPLC Compound A1 (area%) 86.4 86.4 86.4 86.4 Compound A2 (area%) 5.6 5.6 5.6 5.6 Compound A3 (area%) 0.6 0.6 0.6 0.6 Compound A crystallization HPLC Compound A1 (area%) 87.0 87.2 87.5 91.1 Compound A2 (area%) 6.5 6.3 6.1 4.1 Compound A3 (area%) 0.9 0.9 0.9 0.6 DSC Starting temperature (°C) 53.9 53.6 55.3 63.2 Peak temperature (°C) 67.1 67.9 68.1 70.9 Heat of fusion (mJ / mg) 67.8 64.5 67.8 73.8 Yield 72.6 72.2 64.6 55.7
[0043] <Comparative Example 1> 202g of a portion of the cleaned organic layer containing compound A1 obtained in Example 1 was taken out and added to another four-necked flask equipped with a stirrer, thermometer and cooler. The solvent of 118g of the organic layer was removed by distillation under reduced pressure to obtain distillation residue. In order to prepare a crystallization solution of compound A1 with the above composition, 117.9g of methanol was added to the distillation residue at 40°C. The solution was then cooled to 15°C over 3 hours, and 1.4g of crystals of compound A1 were added as seed crystals. The mixture was stirred at 15°C for 19 hours (referred to as "1.0 times by weight crystallization solution" in the graph of Figure 5). Then, 27.0g of water was added dropwise over 2.5 hours, and the mixture was stirred at 15°C for 20.5 hours (at this time, the weight of methanol in the crystallization solution was 0.8 times the weight of the total weight of methanol and water. This is referred to as "0.8 times by weight crystallization solution" in the graph of Figure 5). Then, 43.3g of water was added dropwise over 5 hours, and the mixture was stirred at 15°C for 18 hours (at this point, the weight of methanol in the crystallization solution was 0.6 times the total weight of methanol and water; this is recorded as "0.6 times the weight of crystallization solution" in Figure 5). Next, 54.1g of water was added dropwise over 2.5 hours, resulting in the formation of a highly viscous oil in the crystallization solution (at this point, the weight of methanol in the crystallization solution was 0.45 times the total weight of methanol and water). Compound A1 could not be separated from this crystallization solution. During the above crystallization process, the supernatant was sampled, and the concentration of compound A1 in the supernatant was analyzed by liquid chromatography to confirm the concentration change over time. The results are shown in Figure 5. Adding water to the methanol solution of compound A1 and the water-methanol solution to change the methanol-water ratio resulted in a decrease in the concentration of compound A1 in the supernatant, but oil formation prevented compound A1 from crystallizing out. On the other hand, it was also learned that during the period when the crystallization operation was carried out continuously according to this solvent ratio, almost no decrease in the concentration of compound A1 occurred.
[0044] <Comparative Example 2> Using the crystals of compound A1 obtained in Example 1, an ethanol solution containing 40% by weight of compound A1 was prepared by dissolving the crystals in ethanol at 45°C in a glass solenoid. The solenoid was sealed and cooled in a refrigerator (approximately 4°C) for 3 days, resulting in crystal precipitation. The precipitated crystals were filtered and dried. The obtained crystals of compound A1 were analyzed by HPLC using the above method, and the results clearly showed that they contained 90.9% by area of compound A1, 2.9% by area of compound A2, and 0.3% by area of compound A3. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed an initial temperature of 65.4°C, a peak temperature of the endothermic peak of 70.1°C, and a heat of fusion based on the observed endothermic peak of 80.6 mJ / mg. The DSC analysis chart is shown in Figure 6.
[0045] <Comparative Example 3> Using the crystals of compound A1 obtained in Example 1, a methanol solution containing 40% by weight of compound A1 was prepared by dissolving the crystals in methanol at 45°C in a glass solenoid. The solenoid was sealed and cooled in a refrigerator (approximately 4°C) for 3 days, resulting in crystal precipitation. The precipitated crystals were filtered and dried. The obtained crystals of compound A1 were analyzed by HPLC using the above method, and the results clearly showed that they contained 90.8% by area of compound A1, 2.9% by area of compound A2, and 0.3% by area of compound A3. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed an initial temperature of 67.2°C, a peak temperature of the endothermic peak of 71.5°C, and a heat of fusion based on the observed endothermic peak of 77.6 mJ / mg. The DSC analysis chart is shown in Figure 7.
[0046] <Comparative Example 4> Using the crystals of compound A1 obtained in Example 1, a solution of ethyl lactate containing 40% by weight of compound A1 was prepared by dissolving the crystals in ethyl lactate at 45°C in a glass solenoid. The solenoid was sealed and cooled in a refrigerator (approximately 4°C) for 3 days, resulting in crystal precipitation. The precipitated crystals were filtered and dried. The obtained crystals of compound A1 were analyzed by HPLC using the above method, and the results clearly showed that they contained 93.3% by area of compound A1, 2.0% by area of compound A2, and 0.2% by area of compound A3. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed an initial temperature of 68.7°C, a peak temperature of the endothermic peak of 72.9°C, and a heat of fusion based on the observed endothermic peak of 85.1 mJ / mg. The DSC analysis chart is shown in Figure 8.
[0047] <Comparative Example 5> In Example 1, the same amount of the same sample as in Example 1 was used and the distillation residue was obtained by the same method until the solvent of the organic layer was removed by distillation under reduced pressure. The distillation residue was analyzed by HPLC using the above method, and the results showed that compound A1 had an area of 86.4%, compound A2 had an area of 6.2%, and compound A3 had an area of 0.7%. To prepare a crystallization solution of compound A1 with the aforementioned composition, 292 g of propylene glycol monomethyl ether (PGME) was added to dissolve it. A portion of this solution was transferred to a polypropylene spiral tube and sealed. The spiral tube was cooled in a refrigerator (approximately 4°C) for 4 years, resulting in crystallization. The precipitated crystals were filtered and dried. The crystals of compound A1 obtained were analyzed by HPLC using the above method, and the results showed that compound A1 had an area of 94.3%, compound A2 had an area of 0.9%, and compound A3 had an area of 0.1%. The crystallization of the obtained compound A1, analyzed by differential scanning calorimetry (DSC), showed an initial temperature of 70.4 °C, a peak temperature of 75.2 °C for the endothermic peak, and a fusion heat based on the observed endothermic peak of 92.5 mJ / mg. The DSC analysis results are shown in Figure 9.
[0048] <Comparative Example 6> A portion of the cleaned organic layer containing compound A1 obtained in Example 1 was taken into a polypropylene spiral tube and sealed. The spiral tube was cooled in a refrigerator (approximately 4°C) for 2 weeks, resulting in crystallization. The precipitated crystals were filtered and dried. The yield of compound A1 crystals was 15%. The obtained crystals of compound A1 were analyzed by HPLC using the above method, and the results showed that compound A1 accounted for 94.4% of the area, compound A2 for 1.6% of the area, and compound A3 for 0.2% of the area. The crystals of compound A1 obtained by differential scanning calorimetry (DSC) analysis showed an initial temperature of 71.1°C, a peak temperature of 75.0°C for the endothermic peak, and a heat of fusion based on the observed endothermic peak of 92.1 mJ / mg. The DSC analysis chart is shown in Figure 10.
[0049] <Comparative Example 7> 330g of a portion of the cleaned organic layer containing compound A1 obtained in Example 1 was taken out and added to another four-necked flask equipped with a stirrer, thermometer, and cooler. The solvent of 106.8g of the organic layer was removed by distillation under reduced pressure to obtain a concentrated solution. 49.8g of cyclohexane was added to the concentrated solution at 55°C (at this point, the weight of butyl acetate in the crystallization solution was 0.7 times the total weight of butyl acetate and cyclohexane; this is recorded as "0.7 times the weight of crystallization solution" in the graph of Figure 11). The solution was then cooled to 35°C, and 0.1g of crystals of compound A1 were added as seed crystals. The solution was cooled to 15°C over 3 hours and stirred at 15°C for 17 hours. Then, 66.4 g of cyclohexane was added dropwise over 1 hour, and the mixture was stirred at 15°C for 22 hours (at this point, the weight of butyl acetate in the crystallization solution was 0.5 times the total weight of butyl acetate and cyclohexane; this is recorded as "0.5 times the weight of crystallization solution" in Figure 11). Next, 133 g of cyclohexane was added dropwise over 1.5 hours, and the mixture was stirred at 15°C for 22 hours (at this point, the weight of butyl acetate in the crystallization solution was 0.3 times the total weight of butyl acetate and cyclohexane; this is recorded as "0.3 times the weight of crystallization solution" in Figure 11). During the above crystallization process, samples of the supernatant were taken, and the concentration of compound A1 in the supernatant was analyzed by liquid chromatography to confirm the change in concentration over time. The results are shown in Figure 11. In a solution of compound A1 in butyl acetate and cyclohexane, the ratio of butyl acetate to cyclohexane was varied to reduce the concentration of compound A1 in the supernatant, causing crystals to precipitate from the crystallization solution. However, during continued crystallization at this solvent ratio, almost no decrease in the concentration of compound A1 occurred, indicating slow crystal growth. The precipitated crystals were filtered and dried to obtain 29.9 g of compound A1 crystals (yield 32.8%). HPLC analysis of the obtained compound A1 crystals using the above method showed that compound A1 had an area percentage of 86.5%, compound A2 4.5%, and compound A3 0.8%. Differential scanning calorimetry (DSC) analysis of the obtained compound A1 crystals revealed an initial temperature of 63.7 °C, a peak temperature of 69.2 °C for the endothermic peak, and a heat of fusion based on the observed endothermic peak of 71.4 mJ / mg. The DSC analysis results are shown in Figure 12.
[0050] <Comparative Example 8> 7.06 g of the IPA solution containing compound A1 obtained in Example 4 was taken into a 100 mL test tube, and 1.98 g of ethylbenzene was added. The solution was stirred with a stir bar while cooling to 30°C (at this point, the weight of IPA in the crystallization solution was 0.60 times the total weight of IPA and ethylbenzene). 0.07 g of crystals of compound A1 were added as seed crystals, and the solution was cooled to 15°C over 3 hours. After stirring for 16 hours, 8.83 g of ethylbenzene was added dropwise over 4 hours, resulting in the crystals dissolving (at this point, the weight of IPA in the crystallization solution was 0.20 times the total weight of IPA and ethylbenzene). Crystals of compound A1 could not be separated from this crystallization solution.
[0051] <Comparative Example 9> Take 17.30 g of the n-butanol solution containing compound A1 obtained in Example 11 into a 100 mL test tube, add 4.77 g of ethylbenzene, and cool to 30°C while stirring with a stir bar (at this point, the weight of n-butanol in the crystallization solution is 0.60 times the total weight of n-butanol and ethylbenzene). Add 0.19 g of crystals of compound A1 as seed crystals, and cool to 15°C for 3 hours. Then, add 23.72 g of ethylbenzene dropwise over 1 hour, and the crystals dissolve (at this point, the weight of n-butanol in the crystallization solution is 0.20 times the total weight of n-butanol and ethylbenzene). It is impossible to separate the crystals of compound A1 from this crystallization solution.
[0052] It was found that the crystallization methods for compound A1 obtained by the crystallization methods in Comparative Examples 1 to 9 either fail to crystallize during crystallization or require a long time for crystallization, resulting in low yields of crystals. Therefore, they are unsuitable for industrial manufacturing and are inefficient. Among Comparative Examples 1 to 9, the highest yield was 32.8% in Comparative Example 7, but crystallization was significantly slower and required a long time to obtain crystals. On the other hand, it was found that the crystallization methods for compound A1 obtained by the crystallization methods in Examples 1 to 18 proceeded rapidly in all methods. Furthermore, it was found that compound A1 could be obtained with high yields of 36.7% to 86.9% and with easily operable crystalline properties. Therefore, it was found that these methods are suitable for large-scale industrial production and can efficiently produce crystals of compound A1. [Simplified Explanation of the Diagram]
[0053] Figure 1 is a graph showing the change over time of the concentration of compound A1 in the supernatant of the crystallization solution during the crystallization step in Example 1 by liquid chromatography analysis. Figure 2 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Example 1. Figure 3 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Example 2. Figure 4 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Example 3. Figure 5 is a graph showing the change over time of the concentration of compound A1 in the supernatant of the crystallization solution during the crystallization step in Comparative Example 1 by liquid chromatography analysis. Figure 6 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Comparative Example 2. Figure 7 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Comparative Example 3. Figure 8 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Comparative Example 4. Figure 9 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Comparative Example 5. Figure 10 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Comparative Example 6. Figure 11 is a graph showing the change over time in the concentration of compound A1 in the supernatant of the crystallization solution during the crystallization step in Comparative Example 7 by liquid chromatography analysis. Figure 12 is a graph showing the differential scanning calorimetry (DSC) analysis of the crystallization of compound A1 obtained in Comparative Example 7.
Claims
1. A method for producing crystals of a phenolic compound, wherein, The phenolic compound is represented by chemical formula (A1) and has a methoxymethyl group. The method includes a crystallization step, in which crystallization is performed from a solution containing a phenolic compound represented by chemical formula (A1) having a methoxymethyl group, a chain aliphatic alcohol solvent having 3 to 4 carbon atoms, and an aliphatic hydrocarbon solvent having 6 to 8 carbon atoms.
2. The method for producing crystals as described in claim 1, wherein the aforementioned chain aliphatic alcohol solvent having 3 to 4 carbon atoms is at least one selected from n-propanol, isopropanol, n-butanol and isobutanol, and the aforementioned aliphatic hydrocarbon solvent having 6 to 8 carbon atoms is at least one selected from hexaane, cyclohexane, octane and isooctane.